2015
DOI: 10.1038/srep09620
|View full text |Cite
|
Sign up to set email alerts
|

Rab27A Regulates Transport of Cell Surface Receptors Modulating Multinucleation and Lysosome-Related Organelles in Osteoclasts

Abstract: Rab27A regulates transport of lysosome-related organelles (LROs) and release of secretory granules in various types of cells. Here, we identified up-regulation of Rab27A during differentiation of osteoclasts (OCLs) from bone-marrow macrophages (BMMs), by DNA microarray analysis. Rab27A deficiency in OCLs, using small interfering RNA (siRNA) knockdown in RAW-D cell line or BMMs derived from ashen mice, which display genetic defects in Rab27A expression, induced multinucleated and giant cells. Upon stimulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 50 publications
(54 reference statements)
4
69
0
Order By: Relevance
“…However, there is no evidence of defective bone resorption in such humans and mice. Similarly, mutations of RAB27 and its effectors, which control exocytosis of secretory lysosomes in Griscelli's syndrome and respective mouse models, have no effect on osteoclast function (20). In contrast, inhibition of intracellular trafficking of lysosomes and their fusion with the plasma membrane in osteoclasts attenuate the ruffled border formation and bone resorption ( Figures 4 and 5 and previous reports, refs .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…However, there is no evidence of defective bone resorption in such humans and mice. Similarly, mutations of RAB27 and its effectors, which control exocytosis of secretory lysosomes in Griscelli's syndrome and respective mouse models, have no effect on osteoclast function (20). In contrast, inhibition of intracellular trafficking of lysosomes and their fusion with the plasma membrane in osteoclasts attenuate the ruffled border formation and bone resorption ( Figures 4 and 5 and previous reports, refs .…”
Section: Discussionsupporting
confidence: 51%
“…Ashen mice demonstrates that RAB27A does not directly regulate lysosome secretion during bone resorption (20). Moreover, Chocolate mice harboring a spontaneous mutation in RAB38, which is essential for the biogenesis of lysosome-related organelles, have normal osteoclast differentiation and function (21).…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, small guanosin-5′-triphosphatase (GTPases) Rab7 and Rab27a are necessary for ruffled border formation and/or lysosomal secretion in osteoclasts1213. Furthermore, the localization of Rab7 and LC3 are abnormal, and cathepsin K secretion is significantly decreased in Atg5-deficient osteoclasts21.…”
Section: Resultsmentioning
confidence: 79%
“…In a previous report, the researchers found that Rab27a-deficient osteoclasts showed a markedly impaired bone resorption activity, indicating the important role of Rab27a in maintaining the normal functions of osteoclasts [35,36]. They also showed that depletion of Rab27a results in abnormal phenotypes in osteoclasts.…”
Section: Discussionmentioning
confidence: 93%